Active compounds isolated from red betel (Piper crocatum Ruiz & Pav) leaves active against Streptococcus mutans through its inhibition effect on glucosyltransferase activity - Rima Erviana Setyo Purwono Mustofa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Dental caries is a major problem of dental health in Indonesia. Streptococcus mutans is a bacteria that can causecaries. In this recent time, the agents used to eliminate the caries is less effective due to S. mutans resistance tothose agents. Moreover, the agents may produce side effects after 10 years of consumption.Therefore, effort tofind alternative agents against dental caries is needed. Red betel (Piper crocatum Ruiz & Pav) is a promising naturalmaterial to treat dental caries. The P. crocatum Ruiz & Pav leaves contain secondary metabolites such as essentialoil, flavonoid, alkaloid, and phenolic compounds that active against S. mutans involved in caries formation. Thisstudy aimed to evaluate the activity of secondary metabolites isolated from red betel leaves against S. mutans andits inhibition effect on the glucosyltransferase (GTF) activity. The growth inhibition test of S. mutans was carriedout with liquid dilution test and diffusion test. Cultures of S. mutans were treated with essential oil, alkaloid,flavonoid, phenolic compounds isolated from P. crocatum Ruiz & Pav in various concentration and incubated at 37OCin anaerob condition. Povidone iodine was used as positive control and aquadest as negative control. The inhibitiontest of GTF activity was performed by measuring the levels of formed fructose that was analyzed by Somogyinelsonmethod. The data was analyzed using one-way ANOVA with a 95% confidence interval.The results showedthat essential oil and alkaloid had lowest MIC (Minimal Inhibitory Concentration) compared with the other activecompounds (5000 μg/mL) but higher than povione iodine as positive control (2500 μg/mL). The essential oil exhibitedsimilar inhibition zone diameter compared with povidone iodine, either at low or high concentration (p>0.05). Theessential oil had similar inhibition activity to the glucosyltransferase compared with povidone iodine (p>0.05). Inconclusion, the essential oil of red betel leaves had the strongest activity against the S. mutans growth through itsinhibition effect on GTF activity.Key words : red betel (P. crocatum Ruiz & Pav) – antibacterial - S. mutans – essential oil - glucosyltransferase